Oral Health Promotion Intervention In Rural Contexts: Impact assessment. Córdoba, Argentina. - Lila Cornejo; Elena Hilas; Irma Moncunill (Universidad de Concepción., 2014)
Introduction: The study was carried out in Cruz del Eje Department, Cordoba Province, Argentina. It was based on diagnosis of conceptions of health, concentration of fluoride in drinking water and accessibility to dental coverage in 71 rural schools. Additionally, parents and teachers' conceptions of general and oral health, dental clinical status and sialochemistry of students from eight schools were considered. Objective: To evaluate a community intervention strategy for promoting oral health in rural contexts. Through the participation of the teacher as a mediator of healthy pattern, this strategy was developed. Methods: In order to elaborate oral health promoting strategies, educational workshops, epistolary communication and on site tutorials meetings were implemented. Specific health projects to be added to the Educational Institutional Programs, as a contextualized mediating strategy for promoting oral health were designed by teachers. The strategy was evaluated comparing dental caries increase (CI) detected the previous year and the one following the implementation of the educational plans. Mac Nemar's test was applied, and p<0.05 was set to indicate statistical differences between both periods. Results: A 30.43% CI (p<0.0001) was observed the year before implementing the educational programs as well as a CI reduction to 17.39% (p=0.0002) a year after their application. Conclusion: The drop off in 57.14% of the CI in rural areas, confirms the intervention strategy of designed for this particular context.Keywords: community intervention, oral health promotion, rural communities.